Migration Takes Extra Guts for Juvenile Songbirds: Energetics and Digestive Physiology During the First Journey - McCabe, Brendan J.; Guglielmo, Christopher G. (Frontiers in Ecology and Evolution, 2019)
Many birds undertake long migrations when they are only a few months of age. Although they are typically of adult body size, their performance and survival are often poor compared to adults. This differential performance could be due to lack of experience, selection against poor-performing cohort members, or inherent constraints of continuing physiological and morphological maturation of juveniles. Limited evidence suggests that digestive and muscle physiology of juveniles during their first migration may differ from that of adults. We compared body composition, metabolic rate, and digestive physiology between juvenile and adult passerines during fall migration. First, we measured fat and lean masses by quantitative magnetic resonance, and organ and muscle masses of salvaged carcasses of fall migrants from four passerine species. In general, juveniles had more lean mass and heavier digestive organs (especially liver) than adults in hermit thrushes (Catharus guttatus), Swainson’s thrushes (Catharus ustulatus), ovenbirds (Seiurus aurocapilla), and white-throated sparrows (Zonotrichia albicollis). Principal components analysis of all organs and muscles revealed that juveniles for three of four species had overall larger digestive components and smaller flight muscles than adults. We then used open-flow respirometry to measure basal metabolic rates (BMRs) of juvenile and adult Swainson’s thrushes and white-throated sparrows captured in fall at a migratory stopover site. Controlling for a significant effect of body mass, juveniles had 6% higher BMRs than adults in both species. We then conducted total collection mass balance feeding trials with fall migratory Swainson’s thrushes and white-throated sparrows. Juvenile thrushes had greater metabolizable energy intake than adults, which was achieved through higher food intake rather than greater utilization efficiency. Age classes of white-throated sparrows did not differ in these measures of digestive performance, although juveniles had greater food intake capacity at low lean body masses. We propose that age-related differences in foraging ecology, diet composition and energy requirements may be responsible for larger digestive organs of juvenile migrants. Larger guts may allow juveniles to consume more food or a more dilute diet, but may contribute to higher BMRs.